2015
DOI: 10.1002/app.41855
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of N‐vinyl caprolactam and methacrylic acid onto silicone rubber films for drug‐eluting products

Abstract: Silicone rubber (SR), a material widely used in the biomedical field, was modified with stimuli-responsive poly(N-vinyl caprolactam) (PVCL) and poly(methacrylic acid) (PMAA) with the aim of improving its ability to host drug molecules. The grafting of PVCL and PMAA onto SR was carried out by means of a c-ray preirradiation method, and the dependence of the grafting yield on the comonomer concentration, preirradiation dose, temperature, and reaction time was evaluated. Modified SR films were characterized by Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…[ 34 ] Therefore, copolymerization of the silicone monomer with a hydrophilic comonomer, such as polyhydroxyethylmethacrylate (PHEMA) and methacrylic acid (MAA), was adopted to address the hydrophobicity. [ 34,45 ] For example, Mendelez‐Ortiz et al. reported MAA‐grafted silicone CLs, with a superb anti‐fouling effect that showed a negligible protein absorption when exposed to albumin and fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34 ] Therefore, copolymerization of the silicone monomer with a hydrophilic comonomer, such as polyhydroxyethylmethacrylate (PHEMA) and methacrylic acid (MAA), was adopted to address the hydrophobicity. [ 34,45 ] For example, Mendelez‐Ortiz et al. reported MAA‐grafted silicone CLs, with a superb anti‐fouling effect that showed a negligible protein absorption when exposed to albumin and fibrinogen.…”
Section: Methodsmentioning
confidence: 99%
“…[34] Therefore, copolymerization of the silicone monomer with a hydrophilic comonomer, such as polyhydroxyethylmethacrylate (PHEMA) and methacrylic acid (MAA), was adopted to address the hydrophobicity. [34,45] For example, Mendelez-Ortiz et al reported MAA-grafted silicone CLs, with a superb antifouling effect that showed a negligible protein absorption when exposed to albumin and fibrinogen. Cooper Vision, a CL manufacturer, recently introduced Smart Silicone ™ , a chemically modified CL with silicone channels combined with hydrophilic materials (note that the specific hydrophilic material is not mentioned due to the commercial privacy) that increase oxygen permeability to almost 100% while using less silicone [46].…”
Section: Contact Lens Materialsmentioning
confidence: 99%
“…Joń ca et al [81] described methacrylatea salinker for fluorescein to accesst he antimicrobial mechanism of the tert-butylamine groups.T he mechanism is still not completely clear,b ut as-formed polymers were more active against gram-positive bacteria. Their cell wall consists of multiple layers of peptidoglycan and biggerp ores,w hich possibly allow at ransfer of the polymer.M ethacrylate and caprolactam copolymers were developed by Melendez-Ortiz et al [82] to form drug-eluting silicones. They achieve the sustained release of diclofenac (25), ibuprofen (26), and toluidine blue.…”
Section: Copolymerizationmentioning
confidence: 99%
“…Their cell wall consists of multiple layers of peptidoglycan and bigger pores, which possibly allow a transfer of the polymer. Methacrylate and caprolactam copolymers were developed by Melendez‐Ortiz et al . to form drug‐eluting silicones.…”
Section: Preparation Of Silicones With Antimicrobial Activitymentioning
confidence: 99%
“…Flores-Rojas et al, 2018;Pino-Ramos, Flores- Rojas, Alvarez-Lorenzo, Concheiro, & Bucio, 2018;Xiong et al, 2015) among others.For biomedical purposes, several synthetic and natural polymers, peptides and small molecules have been attached to PDMS matrices and films. For example, surface modification to avoid biofilm formation has been explored, the addition via grafting of stimuli-responsive polymers such as acrylates derivatives, poly(ethylene glycol), acrylamide derivatives or N-vinyl caprolactam to favour the metal nanoparticle immobilization or the antimicrobial drugs delivery(Cabana et al, 2017;Cao, Wu, Wang, Shi, & Li, 2018;Lee & Vörös, 2005;Li, Zhai, Yi, Gao, & Ha, 1999;Li et al, 2012;Melendez-Ortiz, Alvarez-Lorenzo, Concheiro, & Bucio, 2015;Völcker, Klee, Höcker, & Langefeld, 2001). Skin mimicking is one challenge of tissue engineering for transplants and wound repair; for this aim, silicone has been modified to take advantage of its biocompatibility.…”
mentioning
confidence: 99%